Catalytic wet air oxidation of butyric acid solutions using carbon supported iridium catalysts - Gomes, Helder (2010)
Aqueous solutions of butyric acid were treated by catalytic wet air oxidation using carbon-supported iridium catalysts in a stirred reactor. Under the operating conditions of 6.9 bar of oxygen partial pressure and 200 ◦C of temperature, conversions up to 52.9% after 2 h were obtained depending on the type of catalyst used. The effects of butyric acid initial concentration, loading of catalyst, oxygen partial pressure and temperature were investigated and the empirical rate law for acid conversion is presented. Oxidation intermediates such as propionic and acetic acid were identified. The heterogeneous catalyzed free-radical oxidation of butyric acid is discussed.